Comparative evaluation of shear bond strength of brackets bonded with self etch primer/adhesive and conventional etch/primer and adhesive system - Debarshi Bhattacharjee; Kanchan Sharma; Rajalaxmi Sahu; Komal Neha; Archana Kumari; Anurag Rai (Wolters Kluwer Medknow Publications, 2021)
Introduction: The shear bond strength obtained with an acid primer might not be clinically reliable. The present study evaluated the use of a new self-etch primer as compared with the conventional bonding procedure. The findings indicated that the use of a self-etch primer to bond orthodontic brackets to the namel surface provided lower, but clinically accept-able, shear bond forces (mean, 7.1 ± 4.4 MPa). Hence, this study has been designed to evaluate the shear bond strength of orthodontic brackets bonded with a self-etching primer system, and compare it with the conventional acid etching priming system. Materials and Methods: This study was designed to compare the shear bond strength of orthodontic brackets bonded with conventional acid etching- priming and a self-etching primer. For this purpose, one hundred and twenty noncarious, not subjected to any pretreatment chemical agents (e.g. hydrogen peroxide), no cracks caused by the presence of the extraction forceps, no caries and unrestored human maxillary 1st and 2nd premolars, freshly extracted for orthodontic treatment were collected and stored in distilled water before bonding. Separate molds of cold-cure acrylic were prepared and the extracted premolar teeth were embedded in the cold cure acrylic up to the cement enamel junction. Results: For the control group, the mean shear bond strength was 9.38 ± 6.02 MPa and for the experimental group, it is 6.91 ± 3.58 MPa. Group comparison using Chi-square test for the self-etching primer group adhesive remnant index (ARI) scores shows that more than half of the adhesive left over the tooth surface (score 3 and 4). For the conventional group, ARI scores show that there was no or slight amount of adhesive left over the tooth surface (score 5). The proportion of ARI score is significantly (P < 0.001) more in conventional (68.33%) as compared to self-etch primer (SEP) (28.33%). The proportion of ARI scores 4 and less is significantly more in SEP (71.67%) as compared to Conventional (6.67%) with P = 0.004 as per the Chi-square test. Conclusion: The bond strength of SEP is comparatively lesser than the conventional acid etching technique, but is definitely more or less to the required bond strength to resist masticatory forces. Majority of the studies conducted on self-etching primer are in vitro studies. Results of these cannot be extrapolated to the intraoral environment. Hence, further long-term clinical studies need to be carried out before actually recommending the use of self-etching primer in routine orthodontic bonding.